Implementing an IoT Smart Device for Monitoring and Controlling Diverse Electromechanical Systems - Sassi Lachraf; Mesai Ahemd Brahim; Aissa Belkacemi; Bensalem Touil (University of Shahid Hama Lakhdar - El Oued, 2024)
This work is a master’s project aimed at designing a control, monitoring, and protection panel for electric motors using Internet of Things (IoT) technology. We observed several deficiencies in the protection and control of electric motors, which led us to choose this project specifically. Among the identified issues are the high operating costs associated with traveling long distances for motor activation or shutdown. Additionally, there are costs related to travel time and the need for rapid motor protection against unexpected faults. Our project aims to save time by leveraging IoT to enable early detection of motor failures and prompt repairs. This approach minimizes downtime, avoids the inconvenience and expense of long-distance travel, and provides users with peace of mind regarding their motor operations. The system’s real-time motor protection is a fundamental feature of our solution. Our project is divided into two main parts: hardware and software. In the hardware phase, we studied current and voltage sensors, designed and manufactured a PCB (Printed Circuit Board) using drilling, printing, and Acidification techniques. We assembled electronic components and tested various faults until we achieved accurate results, verified through an oscilloscope device. Additionally, we explored actuator relays, control devices, and motor protection equipment. Moving on to the software aspect, we set up a server for sending and receiving data to an Android application. The Android app displays information on the phone and alerts the user in case of any motor-related issues, particularly regarding motor protection. Finally, we tested the entire system with a water pump, obtaining good and efficient results. The Android app provided real-time current and voltage values for each phase, allowing us to control the pump remotely. These outcomes align with our project goals.هذا العمل هو مشروع ماستر يهدف إلى تصميم لوحة تحكم ومراقبة وحماية للمحركات الكهربائي ة وقد لاحظنا عدة أوجه قصور في حماية ومراقبة المحركات (IoT). باستخدام تقنية إنترنت الأشيا ء الكهربائية، مما دفعنا إلى اختيار هذا المشروع بالتحديد. ومن بين المشكلات التي تم تحديدها ارتفاع تكاليف التشغيل, مما يتطلب التنقل لمسافات بعيدة من أجل التشغيل او الايقاف المحركات. بالإضافة إلى تكاليف التنق ل وايضا و استهلاك الوقت في التنقل والحاجة إلى الحماية السريعة للمحرك ضد الأعطال غير المتوقعة. يهدف مشروعنا إلى توفير الوقت من خلال الاستفادة من إنترنت الأشياء لتمكين الكشف المبكر عن أعطال المحركات والصيانة السريعة. تقلل هذه التقنية من وقت التوقف عن العمل، ويتجنب العناء و تكلفة التنقل لمسافات طويلة، ويوفر للمستخدمين راحة البال فيما يتعلق بحالة محرك اتهم. وتعد حماية المحرك في الوقت الفعلي سمة أساسية للنظام .
Master's thesis in electromechanics
Keywords: Electric motor control; AC current and voltage monitoring; Internet of Things (IoT); Electric motor protection; التحكم في المحركات الكهربائية، مراقبة التيار المتردد والجهد، إنترنت الأشياء (إنترنت الأشياء)، حماية المحركات الكهربائية